The interaction of clumping factor B and iron regulated surface determinants of Staphylococcus aureus with platelets - Miajlovic, Helen (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2009)
Clumping factor B (ClfB) of Staphylococcus aureus is a multi-functional surface protein which binds to cytokeratin 10 and fibrinogen. Cytokeratin 10 is found on the surface of desquamated epithelial cells of the anterior nares where it provides a ligand for S. aureus cells expressing ClfB. ClfB contributes to nasal colonisation by S. aureus, which is a risk factor for infection. S. aureus surface proteins that bind to the blood glycoprotein fibrinogen can stimulate platelet aggregation by a fibrinogen-dependent process. Aggregation of platelets by bacteria is believed to contribute to the development of infective endocarditis of which S. aureus is now acknowledged to be the leading cause.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin.